Analysis of Rainfall Distribution and Climate Classification in Response to Flood Events in Lebong Regency, Indonesia - Limbong, Rospita Naomi; Anwar, Anang; Johan, Septi; Lizalidiawati, Lizalidiawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to analyze the distribution and time series of rainfall in Lebong Regency, using a case study of the flood event on April 16, 2024, and to analyze the condition of climate change in Lebong Regency from 2014 to 2024. This research uses daily rainfall data to examine flood events and monthly data over 11 years from 2014 to 2024 for climate classification analysis with 10 rainfall observation stations using the Schmidt-Ferguson method. The results of the data processing were analyzed using descriptive and quantitative methods. Based on the research results, it was found that the distribution of rainfall before, during, and after the flood event experienced a significant change. Before the incident, the lowest rainfall in Lebong Regency was recorded at the Bungin, Gunung Alam, Rimbo Pengadang, and Semelako Atas Stations with a value of 0 mm/day (no rain). Rainfall increased on the day of the flood in several sub-districts, with the highest recorded at the Lemeu Station in Uram Jaya sub-district, reaching 101 mm/day. Meanwhile, after the day of the flood, the rainfall was 12 mm/day. Meanwhile, the climate classification based on the Schmidt-Ferguson method shows that the rainfall in Lebong Regency falls into the wet to very wet climate category. The very wet climate category in Lebong Regency is represented by the Bungin station, with rainfall amounting to 1166 mm/month in January 2020. Based on the 11-year average data, the highest rainfall occurs in November, amounting to 537.58 mm/year. The study also contributes to understanding local flood risk based on long-term rainfall classification, which has rarely been explored in the Bengkulu region.